Efektivitas Perencanaan Pembangunan Pariwisata di Kabupaten Tapanuli Tengah - Sianipar, Andy Frandana (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2019)
Local development planning cannot be separated from the characteristics of the region. Central Tapanuli Regency is located surrounded by mountains, beaches and the sea, which makes it has a lot of tourism potential, such as the sea, beaches and nautical. The local government has also implemented supporting programs to develop its tourism potential which is expected to be able to add significant local income which is quite significant for the local economy. This study aims to determine the tourism development planning process and the effectiveness of tourism development planning in Central Tapanuli Regency. The research uses descriptive method with qualitative approach. Based on the research that has been done, the results of tourism development planning in Central Tapanuli Regency have not been effective, because some programs are not on target in accordance with the tourism potential they have. The results of monitoring and evaluation are not used as a guideline in determining the program of tourism development activities for the following year.